Lipid Profile Abnormalities Observed in Obese Cameroonian Adults do not Depend on Their BMI or Abdominal Circumference - Moor, Vicky Jocelyne Ama; Essama, Doris Bibi; Agoons, Batakeh B; Bayem, Joel Cedric; Marie, Ntep Gwet; Jingi, Ahmadou Musa; Nkeck, Jan Rene; Nonga, Bernadette Ngo (Archives of Clinical and Biomedical Research, 2022)
Background Obesity and dyslipidemia are both lipid related diseases, and the management of obesity involves considering disorders of lipid metabolism. This study aimed to evaluate the relationship between obesity and lipid profile parameters in Cameroonians adults. Methods We conducted a cross-sectional study at two teaching hospitals in Yaoundé (Cameroon). Consenting adults with a BMI ≥25kg/m² were recruited. Participants taking lipid-modifying drugs were excluded. Total cholesterol, HDL, and triglycerides levels were assessed on a fasting blood sample using standardized and automated enzymatic methods. LDL cholesterol was estimated using the Friedewald formula. Chi² test was used to compare proportions and seek for associations between lipid profile components and BMI, with a significance threshold of 0.05. Results 136 participants (105 females, 77.3%) aged 58.8 ± 11 years on average were included. They were classified as overweight (44.1%), grade I (35.2%), grade II (13.2%), and grade III obesity (7.3%). Their main comorbidities were hypertension (63.9%) and diabetes (60.2%). Among them, 72.7% had a sedentary life style while 31.6% were alcohol consumers. The prevalence of dyslipidaemia was 52.9%, with main subtypes being HDL hypocholesterolaemia (54.4%) and hypertriglyceridemia (47.06%). There were no significant associations between BMI and lipid profile indices. Conclusion Half of the obese Cameroonians adults of the sample suffer from dyslipidemia, but it is not directly related to their BMI.